Avaliação do impacto socioambiental e análise da contaminação no Rio Doce após o acidente de Mariana - MG. - CORREIA, Alessandra de Oliveira Alves (2022)
Many already know about the rupture of the tailings dam ocurred in Mariana in 2015. This case was considered one of the largest accidents in Brazil, with social, environmental and economic effects. To analyze the consequences for the population located downstream in Doce River, a scientific expedition report was analyzed, carried out by the Independent Environmental Impact Assessment Group Samarco / Rio Doce (GIAIA) in the year 2017 with the riverside residents of Mariana - MG in the Doce River and its mouth in Espírito Santo, surveyed between 2016 and 2017. And, in order to assess the degree of contamination by metals, both the fiddler crab as a bioindicator species and the sediment were used. For comparative purposes, samples were collected in three different regions, located in the cities of São Mateus –ES (Mariricu river), Regência-ES (Doce river) and Ubatuba-SP (Quiririm river), which were analyzed by X-ray fluorescence, to determine the chemical elements present and, later, statistically compared by multivariate analysis. In the analysis of the report, it is observed that the people whose main activities that depended on the water resource, such as farmers and fishermen, were the most affected. It is noticed that many are still unaware of the sanitary quality of the places that underwent intervention. In addition, many who received Samarco's visit didn’t have the opportunity to receive financial assistance, and it isn’t understandable how the Company used to choose the beneficiaries. The main physical symptoms manifested after the accident and diagnosed by the interview were skin spots and diarrhea. Regarding the physical-chemical analysis of collected materials, it was identified that the main elements present in both the bioindicator and in the sediments were Fe, Cu and Mn located in the Doce River (Regência). Consequently, it is necessary for companies and environmental agencies to keep track of the elements that showed the greatest variance, since they can be bioaccumulative in the food chain and increase the impacts caused to the populations.